Comprobación de la dosificación de probióticos en pollos de engorde - Sanaguano Rivera, Hernan Wilfrido (2010)
The present work on the Confirmation of the probiotics dosage in chickens of she puts on weight with the purpose of obtaining better results without using antibiotics, this investigation was carried out from the month of September to October of the 2009 in the Experimental Farm Santa Ines located in the City Machala, in the road to Pasaje Km. 5 1/2, belonging to the county of The Gold that had the following objectives: 1. - To determine the biological and economic answer in the probióticos use in diets for chickens of it puts on weight. 2. - To experience by means of laboratory analysis the percentage of organism pathogens that you can survive in the digestive tract of the chicken before the presence of a probiotic. She had three experimental units in which 10 chickens were located, with the poultry norm of eight chickens for square meter; weekly she/he registered the consumption of foods, it dilutes, increase of weight and mortality for the lapse of six weeks. In the course of this investigation the handling and application of the probióticos and bacterial it was the following one; 4 g of dissolved probiotic was placed then in 1 liter of water this dissolved mixture you proceeded to place in the drink water the quantity of 35 ml, such a procedure was carried out it with the bacterial one and in the witness's treatment any substance was not placed, since the animals arrived I distribute them to him in each, they had to receive this prepared solution which finished its application until the 42 days of life. It was obtained answers in the lot of the bacterial one it was the best in the conversion of chickens and I don't present any percentage of mortality, during the whole period of upbringing of the birds.